Digital Marketing Course: Strategy for Creating Entrepreneurial Skilled Students in Indonesia - Sasongko, Restu Widyo; Briliana, Vita; Utami, Cahyaning Rini; Masduki , Damayanti; Utomo , Bekti (Journal Of Human And Education (JAHE), 2024)
Technological developments in the Modern Era have developed very rapidly, especially in the technology and digital fields. In today's sophisticated era, the number of unemployed is always increasing every year, especially among high school graduates. One way to overcome this is to become an entrepreneur. However, becoming an entrepreneur today does not only rely on word of mouth and door to door marketing but by using digital marketing techniques. Digital marketing has been proven to be an effective way to expand brand reach and increase sales figures. Therefore, the aim of this community service is to help the government and schools in creating graduates who have entrepreneurial and digital marketing skills so they can work professionally in facing the current era of digital transformation in all fields. In obtaining the data used were observation and literature study. This service activity is a digital marketing training and education effort as a strategic effort in creating young entrepreneurs at the high school level to become skilled entrepreneurs in Indonesia. This effort is motivated by a lack of knowledge about digital marketing itself, which if seen can have great potential for young entrepreneurs at the high school level at Yapasa High School, Gunung Putri District, Bogor Regency, West Java Province. In creating entrepreneurial programs and at the same time supporting government programs to create quality for young and talented entrepreneurs. It is hoped that after this digital marketing training activity for young entrepreneurs, the participants will understand the concept of entrepreneurship, how to market using marketing strategies and understand the various financing methods that can be used by business actors. The training program is expected to provide insight to new business actors. in managing new businesses in the future.